2019
DOI: 10.15421/2019_100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cinnamon on the behavior of Amur Tiger (Panthera tigris altaica, Temminck, 1844) in captivity

Abstract: Our primary interest is in welfare of Amur tiger (Panthera tigris altaica, Temminck, 1844) in the Barnaul Zoo and Leningrad Zoo. As discussed below, behavioral researches can reveal much about the welfare of captive wild animals. Amur tiger s behavior is studied and time budget is calculated for males and females. The Schorygin’ similarity coefficient of behavior is determined (82.64% and 86.76%). We analyzed the differences in their behavior before and after olfactory enrichment. Cinnamon oil reduces pacing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Nonetheless, it has been demonstrated that indicators of impoverished captive tiger welfare were sensitive to habitat size [40,41], broadly supporting the conclusions of Clubb and Mason [35]. However, tiger welfare also appeared to be sensitive to habitat quality [40,42], as well as enrichment and feeding regimes [32,40,[43][44][45][46][47][48], suggesting that much can be achieved to augment captive tiger welfare by understanding their psychological needs and manipulating their habitats and management accordingly [13,23,28]. In 2018, an assessment of the psychological priorities of Amur tigers was carried out at the Korkeasaari Zoo in Helsinki, Finland.…”
Section: Introductionmentioning
confidence: 82%
“…Nonetheless, it has been demonstrated that indicators of impoverished captive tiger welfare were sensitive to habitat size [40,41], broadly supporting the conclusions of Clubb and Mason [35]. However, tiger welfare also appeared to be sensitive to habitat quality [40,42], as well as enrichment and feeding regimes [32,40,[43][44][45][46][47][48], suggesting that much can be achieved to augment captive tiger welfare by understanding their psychological needs and manipulating their habitats and management accordingly [13,23,28]. In 2018, an assessment of the psychological priorities of Amur tigers was carried out at the Korkeasaari Zoo in Helsinki, Finland.…”
Section: Introductionmentioning
confidence: 82%
“…This suggests that environmental enrichment could reduce expression of stereotypic behaviours and even improve welfare. This theory is supported by many studies within the scientific literature, with welfare recommendations including provision of a multisensory space, dense vegetation, a variety of pathways to enable individual choice, presentation of novel items, and even olfactory enrichment [31,34,56,60,62,63].…”
Section: Enclosure Size and Complexitymentioning
confidence: 91%